Analisis Sentimen Mengenai Kepuasan Layanan Aplikasi Salaman Kota Bandung - Maulidina Rahayu; Muhammad Alif Rafi Budiman; Mochammad Fachri Syaripudin (Gunung Djati Conference Series, 2024)
This research aims to present strategies for increasing community participation in using the Bandung City Salaman application. This research uses a mixed method approach which will produce better data. Sentiment analysis of the Salaman app shows a high level of satisfaction, with most reviews giving the maximum rating. The success of this application highlights the potential of technology in supporting Good Governance. Active community participation in e-Government programs is considered the main pillar for increasing transparency, accountability and service quality. The Salaman application has the advantage of providing a variety of population service options that are more abundant than similar applications at the Bandung City Population and Civil Registration Service (Disdukcapil). This advantage gives people more choices to fulfill their population administration needs and is one of the reasons the Salaman application is used by many people and gets good reviews from the public.